2018
DOI: 10.1002/ece3.4082
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation and toxin production provide a fitness advantage in mixed colonies of environmental yeast isolates

Abstract: Microbes can engage in social interactions ranging from cooperation to warfare. Biofilms are structured, cooperative microbial communities. Like all cooperative communities, they are susceptible to invasion by selfish individuals who benefit without contributing. However, biofilms are pervasive and ancient, representing the first fossilized life. One hypothesis for the stability of biofilms is spatial structure: Segregated patches of related cooperative cells are able to outcompete unrelated cells. These dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…We observed a lag in biofilm growth in Ca+Ct co-culture compared to Ca alone; however, surface coverage of the biofilm past 8.5 h ultimately exceeded what C. tropicalis was capable of producing alone, indicating a clear benefit for C. tropicalis . The potential advantages of rapidly establishing and participating in a mature biofilm are numerous, including protection from environmental stresses (Pemmaraju et al, 2016), antifungal agents (Chandra et al, 2001), and other competing microbiota (Deschaine et al, 2018). Conversely, mono-culture biofilms of C. tropicalis have also been shown to be more resistant to antifungal diffusion than C. albicans biofilms (Al-Fattani and Douglas, 2006), which could offer a benefit to C. albicans in Ca+Ct biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a lag in biofilm growth in Ca+Ct co-culture compared to Ca alone; however, surface coverage of the biofilm past 8.5 h ultimately exceeded what C. tropicalis was capable of producing alone, indicating a clear benefit for C. tropicalis . The potential advantages of rapidly establishing and participating in a mature biofilm are numerous, including protection from environmental stresses (Pemmaraju et al, 2016), antifungal agents (Chandra et al, 2001), and other competing microbiota (Deschaine et al, 2018). Conversely, mono-culture biofilms of C. tropicalis have also been shown to be more resistant to antifungal diffusion than C. albicans biofilms (Al-Fattani and Douglas, 2006), which could offer a benefit to C. albicans in Ca+Ct biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In a growing, spatially structured community, individuals at the edge of the leading front have access to nutrients and space [58]; thus, production of substances that facilitate cell–cell adherence can be a competitive strategy [62,63]. Indeed, competitions between biofilm-forming and non-biofilm-forming yeast strains have shown a fitness benefit to biofilm production, with the biofilm-forming strains dominating the outer edge of the community [64]. We tested the effect of natural FLO11 alleles and found that certain alleles were competitively dominant in mats, suggesting that the natural variation we observed can have a profound effect on social phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a decreased competitive ability was found in E. coli TOP10 (tet(X6)/pBAD) and S. Enteritidis ATCC13076 (tet(X6)/pBAD) when the L-arabinose concentration was above 0.1 mM (Figures 3A1, B1). Previous studies have reported that bacterial biofilm production is related to its survival status, thus, the ability of biofilm formation can also reflect bacteria fitness [26,27]. A crystal violet staining method was applied to evaluate the ability of biofilm formation in different host bacteria carrying the tet(X6) gene.…”
Section: P Mirabilis Hs1-t (Tet(x6)/pbad) 4mentioning
confidence: 99%